2019
DOI: 10.3390/ijerph16183318
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Health Care Services; An Application of Physician’s Behavior as a Moderator

Abstract: Patient satisfaction is a measure of the extent to which a patient is content with the health care they received from their health care provider. Patient satisfaction is one of the most important factors to determine the success of a health care facility. The purpose of this study was to determine patient satisfaction with healthcare services and encompass the physician’s behavior as moderation between patient satisfaction and healthcare services. The study seeks to measure the health care services, like a lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
1
27

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(199 citation statements)
references
References 76 publications
11
160
1
27
Order By: Relevance
“…In addition, strong discriminant validity was confirmed, because the values of the square root of AVE for each construct were higher than the values of the squared correlation (R 2 ) between a pair of constructs [118,120]. Lastly, the values of the composite reliability for all of the constructs were greater than the 0.70 threshold value [121], which suggests a high level of internal consistency [122]. Figure 2 and Table 5 display the results of the structural equation modeling (SEM) [123].…”
Section: Measurement Modelmentioning
confidence: 89%
“…In addition, strong discriminant validity was confirmed, because the values of the square root of AVE for each construct were higher than the values of the squared correlation (R 2 ) between a pair of constructs [118,120]. Lastly, the values of the composite reliability for all of the constructs were greater than the 0.70 threshold value [121], which suggests a high level of internal consistency [122]. Figure 2 and Table 5 display the results of the structural equation modeling (SEM) [123].…”
Section: Measurement Modelmentioning
confidence: 89%
“…According to Mulisa et al, (2017), Patient satisfaction is a set of attitudes and perceptions of patients towards health services. Manzoor et al (2019) defined Patient satisfaction as "the state of pleasure or happiness that the patients experience while using a health service". The study of Naik et al (2010) showed that the patient's satisfaction is the degree of congruence between the expectations of the client and the perceived performance of the service provided to them.…”
Section: Patient's Satisfactionmentioning
confidence: 99%
“…Patients' satisfaction regarding healthcare quality has become one of the critical issues for governments all over the world and they are trying to keep their citizens happy (Ampah & Ali, 2019). The patient's opinion has become more important in the improvement of a health care system (Manzoor et al, 2019). Patients' feedback and their perceptions are important requirements for many accreditations and evaluating programs for hospital services (Abbasi-Moghaddam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has different customers (patients, health professionals, public health authorities, and others who would like to get and use laboratory data for the community health) whose opinions are vital components in providing laboratory managers with opportunities to identify areas of improvement [4]. Satisfaction is the degree to which the customers feel their needs ful lled by the service provider [5,6].…”
Section: Page 3/23mentioning
confidence: 99%